Hibridizações curriculares nos cotidianos de uma escola de ensino médio : ou sobre a força dos jovens na invenção de uma vida bonita - Girelli, Danielle Piontkovsky (2013)
The text presents the paths of research conducted in a public high school in the municipality of Santa Teresa, indwelling of the Espírito Santo. States that, the daily actions and inventiveness of the subject practitioners, are woven curricular processes that give movement to the research, considering such practitioners as leaders of curriculum theories-practices. Questions the ways of being young when discussing the processes of individualization that happen in everyday relationships, advocating a theoretical-epistemological perspective that considers youth as hybrid subjects who dwell between cultural places, avoiding its location in idealized or fixed identities. Bet on relationships and everyday creations, movements and tessitura of curricula that take place in collective networks and shared knowledge-doings-senses, woven between young-practitioners, their teachers and other inhabitants of everyday school beyond uniformity, standardization and hierarchies of the official policies of resumes. Assumes the hybridisation process that happens in those relationships, in discussions related to everyday theories-practices and associated education and curricular production to wider cultural processes, recognizing the limits of creating a unique and precise definition of "curriculum". In this sense , advocates curriculum do as production of meaning, arguing for the creation of hybridized resumes that are in the midst of hybrid cultural practices, where the movements, habits and negotiations should be considered in the complex processes that constitute them, amid to the anonymous creations that proliferate in everyday. Theoretical-methodological-policy option assumes as research with everyday using narratives-textual-imagistic produced in different areas of research by practitioners. Highlighted, that the creation of the thesis is done in the proper motion of writing a fictional process, discussing issues related to youths, to vocational education, secondary education, the methods of research, the everyday relationships, networks of singularities, the curricula, the model school at images-narratives these processes, among others, without, however, defining the limits of these enunciative field, whether composing, an intriguing and complex blend of sounds, tastes, doings, sayings and shut the paths meet, comprising most "everyday brand everyday".